Mother's and daughter's : interplay of physical activity with personal, behavioral, and environmental factors - Enright, Amy (2017)
The purpose of this study was to explore the family dynamics in order to further understand and discover through interviews a parent and their children's behaviors in the topic area of physical activity choices. A narrative case study approach was taken to look into each family's experiences in order to better understand their motivations behind physical activity and to make conclusions of the social, environmental, and behavioral dynamics.